Percutaneous Closure of an Iatrogenic Aorta to Right Ventricle Fistula Acquired Following Intracardiac Repair - Rajasekhar, Durgaprasad (Acta Cardiol Sin, 2016)
Iatrogenic aortocardiac fistulae have been described rarely following intracardiac repair. This 28 year-old-male presented to our facility with dyspnea going on 20 days after closure of ventricular septal defect (VSD) and resection of subaortic membrane. A communication was noticed between the aorta and the right ventricle (RV) upon transthoracic echocardiography. Cardiac catheterisation revealed a significant shunt and an aortogram revealed a 6 mm communication between aorta and right ventricle. Percutaneous closure of this defect was attempted under local anaesthesia through right femoral access. An alpha arteriovenous loop was formed despite repeated attempts, hence a retrograde approach for device delivery was considered. An 8 mm Amplatzer muscular VSD occluder device was deployed across the defect achieving a complete closure through an 8F delivery sheath. To the best of our knowledge this is the first report of an iatrogenic aorta to RV fistula occurring in a patient following an intracardiac repair which has been successfully treated percutaneously.